Unio mystica. Skabelse af en topos - Schmidt, Rigmor Kappel (K&K - Kultur og Klasse, 2017)
The secular carpe diem and the religious unio mystica are historically very active in the Renaissance and the Baroque. Both form important steps in the development towards a secularized culture, abandoning the idea of eternal life with the carpe diem, and giving up the ecclesiastical hierarchy in favour of direct contact to God in the unio mystica, cf. Rudolf Otto. The topos unio mystica is restructured and secularized in the “Aleph” by the Argentinian author Jorge Luis Borges introducing the complex figure of the repeated visual verb ver combined with a synedochical selection among the entirety of the vision. The complex figure reoccurs in Hundred Years of Solitude by Gabriel García Márquez, in the Black Book by the Orhan Pamuk, and without the figure in The War at the End of the World by Mario Vargas Llosa, each of them altering the topos according to their narrative needs. As stated in Ernst Robert Curtius, the topos can be seen as historically variant, and with Marie Lund Klujeff it is proposed that the figure as such can contribute actively in the creation and restructuring of the topos, thus not only being confined to the elocutio, but also contributing to the inventio.